Implementation of the Tahsin Al-Qur’an as the Foundation of Religious Literacy for Students at MTs Al-Amanah Waikaya - Masyunida Damier; Wahyunida Damier (Edumaspul: Jurnal Pendidikan, 2026)
Implementation of the Tahsin Al-Qur’an Program as the Foundation of Religious Literacy for Students at MTs Al-Amanah Waikaya. This study was conducted to improve and refine the recitation of the Qur’an. Another objective is to implement the rules of tajwid in accordance with established guidelines, avoid incorrect recitation—whether minor or major errors—as these can alter the meaning of the text, correct recitation that does not align with the principles of tajwid, enhance the quality of recitation so that it sounds more beautiful when heard, and, no less importantly, enable students to cultivate a deeper love for the Qur’an. The background of this study highlights the importance of fostering Qur’anic recitation education in accordance with correct principles, thereby shaping the character and spiritual understanding of the students. A descriptive qualitative approach was adopted as the method for this research, as this method provides a deeper insight into the implementation of the Qur’anic recitation improvement program. Data was collected using various methods, including interviews, observation, and documentation. The Qur’an Recitation Improvement program is conducted daily before the start of regular classes. The stages involved include planning, implementation, evaluation and refinement, and repeated recitation. During the implementation stage, the teacher slowly recites the Qur’an, and the students follow along both collectively and individually; the purpose is to improve fluency and accuracy in pronouncing the letters. Next, the teacher observes the students’ recitation, directly correcting mistakes and providing examples of correct recitation; this constitutes an evaluation of the recitation aspect. In the final stage of the Qur’an recitation improvement activity, the process does not end with the recitation itself; there is a more important aspect involving evaluation and follow-up, where the teacher assesses the students’ recitation skills, provides corrections, feedback, and reinforcement regarding any remaining errors, and consistently motivates the students. Following the analysis, the study yielded results indicating that the implementation of the tahsin program at the school produced significant improvements, with positive effects observed in students who previously struggled with reading such as those who read haltingly, stuttered, or had difficulty with the proper length of syllables who now demonstrated marked improvement compared to before. Therefore, this tahsin program is a solution for students that is highly beneficial in their lives; their recitation becomes more organized and fluent, thereby increasing their love for reciting the Qur’an. The implementation of the Qur’an tahsin program improves the quality of each student’s recitation.